The Impact on Family among Down syndrome Children with Early Intervention - Azmawati Mohammed Nawi; Aniza Ismail; Syazana Abdullah (Tehran University of Medical Sciences, 2013)
Background: Child with Down's syndrome is an individual who is suitable and eligible to receive early intervention services. This study aimed to measure the family outcome among parents of Down syndrome children, on the impact of receiving early intervention and identify the factors influencing it.Methods: A cross sectional was conducted from April 2009 until January 2010 with a total of 125 parents of children with Down syndrome. There are five domains of family outcomes that has been studied which are understanding the strengths, abilities and special needs of children, knowing the rights and talk on children behalf, assisting the child to grow and learn, having a support system and be involved in the community. Children with Down syndrome aged four to 15 years was chosen as the respondents when they were accompanying their children in seven rehabilitation centers or during house visits.Results: Family outcomes among parents of Down syndrome children who receive early intervention is better, 67.3 percent, compared to parents of Down syndrome children who receive late intervention, 41.4 percent. There are significant relationship between the acceptance level of intervention, parents education level, family income and the family outcomes. Parents of children who receive early intervention were more positive in understanding the strengths, abilities and special needs of their children compared to other family outcomes.Conclusion: Families whom children received early intervention had indirectly proved the importance and benefit of early intervention, not only for children with special needs, but for their family as well